Menjaga Budaya Melalui Pentas Tari Oleh Guru Labschool UNISNU Jepara - Pratiwi, Dewi; Amalia, Dina; Afrianingsih, Anita (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
The arts scene has long been a rich platform for artistic and cultural expression in society. The role of dance as a form of artistic expression that connects movement, music, and narrative to convey cultural messages and meanings. This activity aims to provide an opportunity for early childhood education  to apply basic dance movements and their development as early childhood education learning materials. PAUD educators are invited to create variations of innovative dance movements. This service will take place from May to July 2023 with the partner Labschool Unisnu Jepara with a total of 6 educators. Through historical reviews and contemporary analysis, this service explores the role of dance performances in forming and maintaining cultural identity, as well as its impact on learning in PAUD. The implementation details are: 1) Determining groups and types of dance for each group, as well as preparing activity schedules and guidance. 2) Determining the back song for each dance. 3) Discussion and planning dance movements. 4) Review the dance creations. 5) Evaluation of the results of the revision of the dance creation. 6) Dance performance. It is hoped that further efforts will emerge to preserve, develop, and celebrate the richness of art and culture through artistic performances. Through dance, educators' creativity is developed so that they are able to work better and have artistic value. The ability to develop traditional and modern dance movements is a challenge in itself and can be a provision for them to apply their knowledge in the future when they teach as PAUD teachers. Written in English with a distance between sentences of 1 space and the number of words between 150-250. The abstract should contain introductions, methods, results and discussions and conclusions (without citation). Avoid using citations in the abstract.